On a Level Playing Field? The Effect of Parents´ Education on Master´s Degree Graduates´ Labour Market Success in Finland - Isopahkala-Bouret Ulpukka; Nori Hanna (Scientific Research Publishing, Inc., 2022)
It is usually assumed that graduates with similar degrees are on a level playing field in the labour market. However, this common perception conceals social differences among the highly educated population. Following Bourdieu’s thesis that those with a privileged background benefit most from their degreed education due to the effects of inheritance of cultural capital, we investigate whether parents’ education affects Master’s degree graduates’ success in the Finnish labour market. We use nationally representative data of Finnish 25 -45-year-old graduates from a broad educational field of business administration and social sciences (N = 7798). The results show that graduates whose parents have not attained post-compulsory education have lower success rates in the labour market than other graduates. However, graduates whose parents have attained higher education have similar success rates as graduates whose parents have attained upper secondary education. In addition, the effect of parents’ education diminishes with graduates’ age and career progression. Our findings provide new knowledge to policymakers, university administrations, and employers interested in graduate employability and social inequality. It is suggested that further research, targeted measures and career support are needed to ensure that graduates coming from low-educated families can have equally successful entry to the labour market.